2022
DOI: 10.7189/jogh.12.11003
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and economic burden of myopia in urban China: A nationwide cost-of-illness study

Abstract: Background China contributes to a significant proportion of the myopia in the world. The study aims to investigate the utilization of various correction methods and health service in urban China, and to estimate the cost of myopia treatment and prevention. In addition, we aimed to estimate the cost of productivity loss due to myopia. Methods The study was a cross-sectional investigation carried out in urban areas in three provinces located in the east (Shanghai), middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Moreover, high myopia (HM) often causes myopic choroidal neovascularization (mCNV), complicated glaucoma, cataract, macular hole (MH), and other blinding complications (Wu et al, 2016), which result in a heavy economic burden to families and society. Statistically, the annual productivity loss as a result of myopia in China is as high as US $26.3 billion (Ma et al, 2022), whereas the global productivity loss caused by myopia alone was as high as US $244 billion in 2015 (Naidoo et al, 2019). These values will increase as the prevalence of myopia increases in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high myopia (HM) often causes myopic choroidal neovascularization (mCNV), complicated glaucoma, cataract, macular hole (MH), and other blinding complications (Wu et al, 2016), which result in a heavy economic burden to families and society. Statistically, the annual productivity loss as a result of myopia in China is as high as US $26.3 billion (Ma et al, 2022), whereas the global productivity loss caused by myopia alone was as high as US $244 billion in 2015 (Naidoo et al, 2019). These values will increase as the prevalence of myopia increases in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reasons for non-compliance may include poor literacy, misconceptions, and lack of eye health knowledge among parents (29). Because economic considerations are important in low-and middle-income countries, the provision of low-cost or free spectacles can improve access (30).…”
Section: Discussionmentioning
confidence: 99%
“…The past study predicated that the number of high myopia people will star from 163 million people that is the 2.7% of the world population in 2000 to 938 million people that is 9.8% of the world population in 2050 (Holden et al, 2016a). Among Asian populations, myopia is especially higher prevalent (7-21%) than other populations (He et al, 2009;Sawada et al, 2008;Wong et al, 2000;Wong and Saw, 2016).It caused a great deal of direct and indirect burden in economy worldwide, notably in East Asia (Ma et al, 2022;Modjtahedi et al, 2021;Modjtahedi et al, 2018;Naidoo et al, 2019). The previous study reported the potential productivity loss relevanted for vision impairment and uncorrected myopia was US$244 billion and was US$6 billion globally in 2015 (Naidoo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%